Mengintegrasikan Keterampilan Hidup dan Kewirausahaan: Model Pendidikan Alternatif untuk Generasi Muda - Yurlina Ndruru; Indri Purnama Putri Harefa; Yosia Belo (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
Globalization has changed the perspective on education, shifting the focus from the conventional face-to-face model to a more open and flexible approach, often referred to as